Скульптура слов’ян-язичників і художня традиція античного світу (до проблеми історико-культурної сув’язі) - Забашта, Р. (Студії мистецтвознавчі, 2009)
The point of historic-cultural unity between Slav-paganish plastic tradition and antic world is not new for the Slav particularly archeological researches. It arose at the beginning of the systematic studies of Slav-paganish antiquities (near the middle of 19 century) and was stimulated by the first founds which were examples of Slav sculptures before Christian epoch. Many scientists were interested in this question since first analytic studies mainly from the Slav circle. Some observations, suggestions, theoretical studies linked with different antic things: coins, crafts founds on the territory of Slav settlements were made as well. But till nowadays they have not become the subject of deep systematic studies in Ukrainian science. The researchers touched these points from time to time in their articles dealing with relationship between Slav and antic worlds, more often while attributing some sculpture and plastic examples of late Rome and early medieval epoch. In preсeding literature the only monument had been considered under this point of view: idol pillar found in 1848 in the river Zbruch. Some authors in spite of different opinions in concrete points agreed that this sculpture has got some formal similarities with images of the antic pantheon sculptures. Such suggestion can be accepted at least in some degree. But they are mostly abstract in their formulation, not based on a comparative analyses of the all concrete characteristics of the monument. More over, they don’t include any explication concerning the issue of Slav sculptors repetitions in morphological schemes and iconographical moments which could be caused by its late dating (9/10–11/13 centuries). To clear up the problem we have to look for some more examples of Slav-antic relationship, first of all among the works which are posed chronologically close. The plastic monuments of the second half of the 1-st century settlements called Pshevor culture found near the village Zagai (Volyn), Tcerniakiv culture in the village Ivankivtsi, remains from the private collection of a little town Murovani Kurylivtsi (Chkmelnytski region) are considered and studied in the article. Taking attention on a) typological comparison of formal (morphological, iconographical, stylistic) features of three measure images with corresponding late antic sculpture items, b) closeness from the point of view of time and territory, in particular the localization of the monuments being analyzed in the field of the Dnister river – a water way well known in the antic world, at last the fact that the territory of the middle Dnister was included into a contact zone, neighbouring with antic world, we can observe in these monuments some exterior influences of the better developed antic sculpture tradition and so see them as an expression of mutual Slav-antic culture unity.